Editorial: First two years of a new open-access journal on speech sciences - Barbosa, Plínio Almeida (Journal of Speech Sciences, 2021)
In its second year of publication, the Journal of Speech Sciences (JoSS) offers its readers the fourth issue (issue 2 of volume 2).Starting a new academic journal is not a simple task, not only because disseminating the information of its very existence is a critical as well as a complex matter, but also because we must ensure the journal will offer high-quality and accessible papers.